Cardiovascular Magnetic Resonance to Guide Defibrillator Implantation for LVEF of 36% to 50% - Joseph B. Selvanayagam; John G. F. Cleland; Graham S. Hillis; Sivabaskari Pasupathy; Laurent Billot; Katherine E. George; John J. Atherton; Colin Berry; Ivaylo Tonchev; Chris Gianacas; Werner Jung; Sanjay K. Prasad; et al. (JAMA, 2026)
Importance Current guidelines do not recommend primary prevention implantable cardioverter-defibrillators (ICDs) unless a patient’s left ventricular ejection fraction (LVEF) is 35% or less. Many sudden cardiac deaths (SCD) occur when LVEF is 36% to 50%. Myocardial scar (a key arrhythmic substrate) can be assessed by late gadolinium enhancement on cardiovascular magnetic resonance (CMR), but robust evidence is lacking regarding a scar-based approach to ICD insertion. Objective To determine whether implantation of ICDs reduces SCD or hemodynamically significant ventricular arrhythmia (HSVA) in patients with an LVEF of 36% to 50% and myocardial scar. Design, Setting, and Participants An open-label randomized clinical trial enrolled adults between 2015 and 2022 who had ischemic or nonischemic cardiomyopathy, an LVEF of 36% to 50%, CMR-defined myocardial scar, and were receiving guideline-directed medical therapy at 18 sites in Australia, Germany, and the UK. Follow-up assessments were completed in 2026. Interventions A primary prevention ICD (n = 180) vs an implantable loop recorder (ILR) (n = 173). Main Outcomes and Measures The primary composite outcome was SCD or HSVA. Five secondary outcomes were evaluated: SCD, HSVA, heart failure–related hospitalization, cardiovascular mortality, and all-cause mortality. Results Of 353 patients randomized (median age, 65 years [IQR, 57-61 years]; 18% female; and 72% had an ischemic etiology), 70% had an LVEF of 40% or greater. The median follow-up was 6.3 years (IQR, 4.8-7.6 years). The primary composite outcome occurred in 14 patients (7.8%) in the ICD group compared with 16 patients (9.2%) in the ILR group (hazard ratio [HR], 0.76 [95% CI, 0.37-1.58]). For the individual components of the primary composite outcome, SCD occurred in 3 patients (1.7%) vs 10 patients (5.8%) in the ILR group (HR, 0.26 [95% CI, 0.07-0.95]) and HSVA occurred in 12 patients (6.7%) vs 6 patients (3.5%), respectively (HR, 1.77 [95% CI, 0.65-4.81]). The rates for all-cause mortality, cardiovascular mortality, and heart failure–related hospitalization were similar between groups. In a prespecified analysis of 6 subgroups, the primary outcome occurred less often in patients younger than 70 years in the ICD group (3.3%) vs patients in the ILR group (10.0%) (HR, 0.28 [95% CI, 0.09-0.89]) but not in those aged 70 years or older (16.9% vs 7.5%, respectively) (HR, 2.33 [95% CI, 0.75-7.26]; P = .01 for interaction). Conclusions and Relevance Implantation of an ICD did not reduce the composite outcome of SCD or HSVA in patients with an LVEF of 36% to 50% and myocardial scar. Trial Registration ClinicalTrials.gov Identifier: NCT01918215